2000
DOI: 10.1099/0022-1317-81-4-895
|View full text |Cite
|
Sign up to set email alerts
|

The picornavirus replication inhibitors HBB and guanidine in the echovirus-9 system: the significance of viral protein 2C

Abstract: HBB [2-(α-hydroxybenzyl)-benzimidazole] and guanidine are potent inhibitors of picornavirus replication. Among other evidence, limited cross-resistance and a synergistic effect of both inhibitors suggest similar but not identical mechanisms of antiviral action. Echovirus-9 variants resistant to each of these drugs were characterized and sequenced. Complete resistance to HBB or guanidine was shown to be due to single but different point mutations in the non-structural protein 2C. Protein 2C was expressed as GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
4
34
0
1
Order By: Relevance
“…Besides these "main" mutations, guanidine-resistant poliovirus was shown to carry some additional mutations that were located at residue 143, 227, or 233. It should be emphasized that residue 227 is also involved in the resistance of echovirus to HBB (39) and, as reported here, of coxsackievirus to TBZE-029. Shimizu et al (61) demonstrated that poliovirus carrying either of the guanidine "main" mutations was not only resistant to guanidine but also cross-resistant to MRL-1237.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Besides these "main" mutations, guanidine-resistant poliovirus was shown to carry some additional mutations that were located at residue 143, 227, or 233. It should be emphasized that residue 227 is also involved in the resistance of echovirus to HBB (39) and, as reported here, of coxsackievirus to TBZE-029. Shimizu et al (61) demonstrated that poliovirus carrying either of the guanidine "main" mutations was not only resistant to guanidine but also cross-resistant to MRL-1237.…”
Section: Discussionsupporting
confidence: 70%
“…Reintroduction of these mutations, either alone or combined, into a full-length clone of CVB3 generated seven recombinant clones, which were further characterized. Single amino acid mutations at positions Interestingly, previous studies with the antiviral compound HBB in echovirus 9 reported that altered sensitivity to this drug mapped, similarly to our findings, to the Ile and Ala residues at positions 227 and 229, respectively (32,39). In particular, the I227L mutation, either alone or combined with the A229V mutation, conferred resistance to HBB.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations